Testing the relationship between government expenditure and national income in Malaysia - Tang, Tuck Cheong (Universiti Utara Malaysia, 2001)
The present study aims to investigate the relationship between national income and Government expenditure in Malaysia. The annual data over the period 1960 to 1998 were used. The result of Johansen multivariate cointegration revealed that no long run relationship among the non-stationary variables existed. Further, a unidirectional causality was observed, that is, from national income growth to Government expenditure growth. Thus, Wagner's law is supported by the data, in the short run. Some relevant policy issues and implications are discussed.